2021
DOI: 10.1371/journal.pgen.1009595
|View full text |Cite
|
Sign up to set email alerts
|

An autoregulatory negative feedback loop controls thermomorphogenesis in Arabidopsis

Abstract: Plant growth and development are acutely sensitive to high ambient temperature caused in part due to climate change. However, the mechanism of high ambient temperature signaling is not well defined. Here, we show that HECATEs (HEC1 and HEC2), two helix-loop-helix transcription factors, inhibit thermomorphogenesis. While the expression of HEC1 and HEC2 is increased and HEC2 protein is stabilized at high ambient temperature, hec1hec2 double mutant showed exaggerated thermomorphogenesis. Analyses of the four PHYT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…The PIF7 sequestration of AN3 potentially leads to the buildup of inactive heterodimers. Interestingly, a comparable regulatory mechanism has recently been described for HEC2 control of PIF4 in thermomorphogenesis ( 54 ). Here, HEC2 both stabilizes PIF4 and inhibits PIF4 function through heterodimerization.…”
Section: Discussionmentioning
confidence: 53%
“…The PIF7 sequestration of AN3 potentially leads to the buildup of inactive heterodimers. Interestingly, a comparable regulatory mechanism has recently been described for HEC2 control of PIF4 in thermomorphogenesis ( 54 ). Here, HEC2 both stabilizes PIF4 and inhibits PIF4 function through heterodimerization.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, plants already develop several brakes to restrict PIF4 activity. For example, transcription factors HECATEs (HEC1 and HEC2) directly interact with PIF4 and inhibit its transcriptional activity ( Lee et al., 2021 ). In this study, we revealed that alternative splicing was also an efficient way to attenuate PIF4-regulated thermomorphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another elegant study showed that HEC1 and HEC2 inhibit thermomorphogenesis by forming a negative feedback loop with PIF4 [ 18 ]. hec1 hec2 double mutants exhibited much longer hypocotyls at 28 °C compared with Col-0 controls, while HEC2ox plants showed short hypocotyls.…”
Section: Pif4-interacting Transcriptional Regulatorsmentioning
confidence: 99%
“…hec1 hec2 double mutants exhibited much longer hypocotyls at 28 °C compared with Col-0 controls, while HEC2ox plants showed short hypocotyls. Furthermore, high temperature upregulated HEC2 expression levels and stabilized HEC2 protein levels [ 18 ]. Genetic analysis showed that PIFs are epistatic to HEC2 .…”
Section: Pif4-interacting Transcriptional Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation